Development Strategies of Study Programs in University of Riau - Zulkarnain, Zulkarnain (Program Pascasarjana, Universitas Riau, 2016)
Implementation of ASEAN Economic Community (AEC) in December 2015 brings the impact and substantial changes to the management of higher education, especially Postgraduate Program of University of Riau. Even though the development of a postgraduate study program is a demand, but in practice must refer to the Law on Higher Education and the Regulation of the Minister concerned. The government with all of its authorities restructures the higher education system to avoid implementation of higher education institution that does not comply with applicable regulations. The most principle aspects in the development and management of studies program at the University of Riau are associated to (a) the development of educational infrastructures and facilities (b) home-base lecturers (c) curriculum, and (d) the achievement of accreditation. The competition appeared between public and private university has become an open competition, including with other universities abroad. Students can choose a study program based on qualifications and reputation earned by each institution without distinguishing public or private, domestic or foreign university. The open competition will bring a real impact on the university’s existence in the future. Policy of development and establishment of study program has to be done by comprehensive evaluation because reputation and competency of graduates are not enough with the educational process, but it should also establish cooperation with abroad institutions that can raise its rating and existence as a provider of qualified higher education. Therefore, various conditions relating to the educational process, quality, recognition of the business world and others should be a forward concern.